2022
DOI: 10.1093/schbul/sbac018
|View full text |Cite
|
Sign up to set email alerts
|

The Puzzle of Functional Recovery in Schizophrenia-Spectrum Disorders—Replicating a Network Analysis Study

Abstract: Background and hypothesis Recovery from psychosis is a complex phenomenon determined by an array of variables mutually impacting each other in a manner that is not fully understood. The aim of this study is to perform an approximated replication of a previous network analysis study investigating how different clinical aspects—covering psychopathology, cognition, personal resources, functional capacity, and real-life functioning—are interrelated in the context of schizophrenia-spectrum disorde… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

1
14
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 12 publications
(15 citation statements)
references
References 56 publications
1
14
0
Order By: Relevance
“…Furthermore, some authors suggest specific relationship patterns. While experiential symptoms (avolition, anhedonia, and asociality) negatively impact work, global functioning, and interpersonal relationships (10)(11)(12)(13), expressive symptoms (affective flattening and alogia) mainly impact social functioning (14)(15)(16).…”
Section: Introductionmentioning
confidence: 99%
“…Furthermore, some authors suggest specific relationship patterns. While experiential symptoms (avolition, anhedonia, and asociality) negatively impact work, global functioning, and interpersonal relationships (10)(11)(12)(13), expressive symptoms (affective flattening and alogia) mainly impact social functioning (14)(15)(16).…”
Section: Introductionmentioning
confidence: 99%
“…Schizophrenia is a severe mental illness (SMI) affecting more than 21 million people worldwide that frequently leads to a persistent disability and impaired cognitive, social, and emotional functioning [ 1 ]. Schizophrenia is currently conceptualized as being characterized by at least positive symptoms (such as delusions and hallucinations), negative symptoms (including anhedonia, alogia, avolition, and social withdrawal), and cognitive symptoms (such as deficits in attention, processing speed, verbal learning, visuospatial learning, problem solving, working memory, and cognitive flexibility) [ 2 , 3 , 4 , 5 ]. Moreover, social cognition (including emotional intelligence, facial emotion recognition, emotion evaluation, and social inference) impairment may significantly impact the functional recovery in schizophrenia patients, due to the negative effects on interpersonal relationships, community adjustment, and vocational functioning [ 6 , 7 ].…”
Section: Introductionmentioning
confidence: 99%
“…The relationships among these variables and functional outcome seem to be very complex and to follow multiple and complicated pathways ( 5 , 16 , 26 , 27 , 37 ). For instance, it has been found that neurocognition influences the functional outcome, in particular the areas of everyday and work skills, mainly indirectly through functional capacity, social cognition, engagement with services, and internalized stigma, which in turn is indirectly associated with the functional outcome through the resilience ( 16 , 27 ).…”
Section: Introductionmentioning
confidence: 99%
“…Furthermore, it has been found, by using network analyses, that functional capacity and everyday life skills emerge as the most central and interconnected nodes ( 5 , 26 , 37 ). Functional capacity is the bridge between cognition (neurocognition and social cognition) and functional outcome ( 5 , 26 , 37 ), in particular the area of everyday life skills which, in its turn, connects other domains of functional outcome with psychopathology and internalized stigma ( 5 , 26 ).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation